Trees on Farms for Enhancing Biodiversity and Food Security in Rwanda - Rutebuka, J.; Hingorani, S.; Ntawuhiganayo, B.E; Mukuralinda, Athanase (World Agroforestry Centre, 2020)
Over 43 percent (43%) of all global agricultural land now has greater than 10 percent tree cover which represents over 2 billion hectares of land and engages more than 900 million of people (Zomer et al., 2014). Particularly, major increase has been made in tree cover on agricultural lands in many parts of the tropics, including Rwanda. In the context of biodiversity for food security, agriculture, forestry and fishing encompass over two-thirds of the population for income generation and food security (BIOFIN, 2017). Agriculture sector accounts approximately one-third of Rwanda’s GDP with more than 80% of the total population that are practicing agriculture farming systems (NISR, 2018). Ecosystems offer a wide range of benefits and opportunities for local and national economic development, improved livelihoods and provision of environmental goods and services that vary on scale from the Albertine Rift in the West to the savannah lake and swamp systems of the Akagera region in the East¹ (GoR, 2011). Biodiversity for food security integrates crops, livestock and trees to support agriculture as the main source of employment, income and improved livelihood in rural areas (Ndayambaje, 2016).